CORPORATE ENVIRONMENTAL DISCLOSURE, CORPORATE GOVERNANCE, AND COST OF DEBT IN CHINA’S PHARMACEUTICAL INDUSTRY - Wang , Shiyi; Lau , Lin Sea; Lee , Ah Suat (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
In China, one of the largest emerging markets, the growing public demand for sustainable development has led creditors to place greater emphasis on corporate environmental performance. This study uses a sample of 1141 firm-year observations of Chinese listed pharmaceutical companies from 2018 to 2022, to empirically examine the impact of corporate environmental disclosure (ED) on the cost of debt (COD), as well as the moderating effect of corporate governance on this relationship. By employing a Fixed Effects regression model, the results show that enhanced ED significantly reduces the COD. Furthermore, corporate governance plays a significant positive moderating role in this process. Similar results are obtained using the two-step system Generalized Method of Moments (GMM) estimation, which can address the potential endogeneity issues. These findings provide valuable insights for Chinese pharmaceutical companies on how enhancing ED and governance can help lower financing costs, leading to a better balance between profitability and environmental protection. Specifically, such improvements are likely to result in more favorable financing conditions, benefiting companies, creditors, and the public in an evolving market. This paper also offers practical recommendations for corporate managers, creditors, and policymakers, aiming to enhance environmental disclosure standards, integrate such disclosures into financial risk assessment frameworks, and strengthen the effectiveness of corporate governance.